Gandouling inhibits hepatic fibrosis in Wilson's disease through Wnt-1/β-catenin signaling pathway. (15th July 2023) - Cheng, Chenglong; Wang, Qiang; Huang, Yurong; Xue, Qiuyun; Wang, Yuting; Wu, Peng; Liao, Faxue; Miao, Chenggui
Abstract: Ethnopharmacologic significance: Wilson's disease (WD) hepatic fibrosis is the result of chronic liver injury induced by Cu 2+ deposition in the liver. Gandouling (GDL) is a hospital preparation of the First Affiliated Hospital of Anhui University of Chinese Medicine. Previous studies have found that GDL can play an anti-inflammatory, anti-oxidation, and promote Cu 2+ excretion, which has a clear anti-WD effect. Aim of the study: We found that Wnt-1 was significantly up-regulated in the liver tissue of toxic-milk (TX) mouse in the WD gene mutant model, and the monomer components of GDL could combine well with Wnt-1. Therefore, in this work, we used RT-qPCR, Western blot, immunofluorescence, network pharmacology, molecular docking, and related methods to study the effects of GDL on hepatic stellate cell (HSC) activation and Wnt-1/β-catenin pathway in TX mice to clarify the effect of GDL on WD hepatic fibrosis. Results: GDL could alleviate hepatic fibrosis, improve liver function, and inhibit the activation of HSC in TX mice. Network pharmacology predicted that the Wnt-1/β-catenin was the target of GDL, and molecular dynamics further revealed that GDL has a good binding ability with Wnt-1 and inhibits the Wnt/β-catenin signaling pathway through Wnt-1. Furthermore, we found that GDL blocked the Wnt-1/β-catenin signaling pathway in the liver of TX mice in vivo. In vitro, serum containing GDL blocked the Cu 2+ ion-induced Wnt-1/β-catenin signaling pathway in LX-2 cells. Therefore, GDL blocked the Wnt-1/β-catenin signaling pathway, inhibited HSC activation, and improved WD hepatic fibrosis by binding to Wnt-1. Conclusion: GDL improves hepatic fibrosis in WD model mice by blocking the Wnt-1/β-catenin signaling pathway, and Wnt-1 may be a new target for the diagnosis and treatment of WD. This reveals a new mechanism of GDL against WD, and promotes the clinical promotion of GDL. Graphical abstract: Wnt-1 expression was significantly up-regulated in TX mice and Cu 2+ -induced LX-2 cells. Wnt-1 significantly activated the Wnt/β-catenin signaling pathway, promoted the activation of HSC, increased the levels of inflammatory cytokines TNF-α, IL-1β, and IL-6, and significantly increased the expression of α-SMA and collagen 1. GDL has an obvious therapeutic effect on TX mice. Combined with the molecular docking results, we found that GDL has a good binding ability with Wnt-1 and inhibited the Wnt/β-catenin signaling pathway through Wnt-1. This indicates that GDL exerts antifibrotic effects through the Wnt-1/β-catenin signaling pathway. Image 1 Highlights: Wnt-1 in Wilson's disease (WD) is significantly increased. Wnt-1 activates the Wnt/β-catenin pathway and promotes the development of WD. GDL reduces the expression level of α-SMA and collagen I by binding to Wnt-1. GDL inhibits WD through the Wnt-1/β-catenin signal axis.